MASS MEDIA IN THE CULTURE OF NEW TIME EPOCH - Ороховська, Л. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article the author examines the phenomenon of mass media in the culture of New time epoch and analyzes the connection between the changes of ways of communication and social-political life of mankind.